Rural women in leadership [ positive factors in leadership development - McVay, Lori Ann (CABI, 2013)
Rural women and leadership have, in recent years, come to be the focus of development initiatives in many countries. To date, however, much of the writing on this topic has focused heavily on obstacles rather than facilitative factors in women's attainent of leadership positions. Citing examples from a case study in Northern Ireland, this book gives voice to the many vital, positive elements in rural women's leadership development.